The extensive and intensive effects of Vietnam's technical measures on agricultural imports - Bich Ngoc Nguyen (Cogent Economics & Finance, 2024)
Technical measures, particularly Sanitary and Phytosanitary measures (SPS) and Technical barriers to trade (TBT) can affect to firms' market entry and the volume of trade. Yet, technical measures is ambiguous and complicated, especially for developing countries. Therefore, the study analyses the extensive and intensive effects of SPS and TBT measures imposed by Vietnam on agricultural imports across products and partners. The empirical analysis employs gravity model with Heckman two-stage estimation at the disaggregated level from 2007 to 2019. The findings show that SPS and TBT have positive effects at the extensive margin while having heterogeneous effects at the intensive margin. Across different products, technical measures imposed on agricultural processed products are significant positive to firms' participation but are insignificant to the scale of trade. Imposing SPS measures on animal products facilitates market entry, while decreasing the intensive margin. In plant products, SPS measures play the market barriers to protect the advantage of exporting products, but firms can expand the import volume after adapting to TBT regulations. The estimation also shows that SPS and TBT increase the probability of imports from developed countries while having insignificant effects on developing countries.
Keywords: 330; Sanitary and phytosanitary measures; technical barriersto trade; agriculturalimports; extensive margin; intensive margin